Recent Overviews in Functional Polymer Composites for Biomedical Applications - Moustafa Zagho (18059980) (2018)
Composite materials are considered as an essential part of our daily life due to their outstanding properties and diverse applications. Polymer composites are a widespread class of composites, characterized by low cost, facile processing methods, and varied applications ranging from daily-use issues to highly complicated electronics and advanced medical combinations. In this review, we focus on the most important fabrication techniques for bioapplied polymer composites such as electrospinning, melt-extrusion, solution mixing, and latex technology, as well as in situ methods. Additionally, significant and recent advances in biomedical applications are spotlighted, such as tissue engineering (including bone, blood vessels, oral tissues, and skin), dental resin-based composites, and wound dressing. Other Information Published in: Polymers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/polym10070739